2021
DOI: 10.1093/bjs/znaa110
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus open resection of intrahepatic cholangiocarcinoma: nationwide analysis

Abstract: Background The relevance of laparoscopic resection of intrahepatic cholangiocarcinoma (ICC) remains debated. The aim of this study was to compare laparoscopic (LLR) and open (OLR) liver resection for ICC, with specific focus on textbook outcome and lymph node dissection (LND). Methods Patients undergoing LLR or OLR for ICC were included from two French, nationwide hepatopancreatobiliary surveys undertaken between 2000 and 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…[23][24][25] When possible, minimally invasive surgery may have a role in enhancing recovery and potentially reducing complications, though this is not always feasible, and comparative data between open and minimally invasive surgery in this setting are lacking. [26][27][28] Unfortunately, despite achieving a margin-negative resection, long-term oncological outcomes are poor, with 5-year survivals between 30% and 40% and low cure rates (9.7%; 95% CI, 6.1-13.4). [29][30][31] Recurrence rates after LR are high, with the initial recurrence being intrahepatic in 60%-70%.…”
Section: Outcomes and Challenges With LI Ver Resections For Iccamentioning
confidence: 99%
“…[23][24][25] When possible, minimally invasive surgery may have a role in enhancing recovery and potentially reducing complications, though this is not always feasible, and comparative data between open and minimally invasive surgery in this setting are lacking. [26][27][28] Unfortunately, despite achieving a margin-negative resection, long-term oncological outcomes are poor, with 5-year survivals between 30% and 40% and low cure rates (9.7%; 95% CI, 6.1-13.4). [29][30][31] Recurrence rates after LR are high, with the initial recurrence being intrahepatic in 60%-70%.…”
Section: Outcomes and Challenges With LI Ver Resections For Iccamentioning
confidence: 99%
“…All studies found better TO rates in patients undergoing a laparoscopic procedure compared with an open procedure. Two of these studies included only patients with ICC 32 , 35 and three studies compared the laparoscopic and open approach in patients with HCC, portal hypertension and cirrhosis, and patients with any liver disease 9 , 31 , 33 . In both studies focusing on HCC, the laparoscopic approach proved to be a predictor of TO in multivariable analysis with Ors of 2.81 (95 per cent c.i.…”
Section: Resultsmentioning
confidence: 99%
“…This is not a coincidental finding and has been mentioned in several previous studies. Hobika et al found a lower probability of LND in the laparoscopic group than in the open group in a nationwide study ( 12 ). In addition, Martin et al suggested that laparoscopic treatment for ICC was associated with worse lymph node evaluations than open surgery ( 22 ), while several other meta-analyses also concluded that the LND rate was lower in the laparoscopic group ( 23 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…In 2002, Chen first reported LH for ICC and successfully performed LND laparoscopically ( 11 ); since then, studies on LH for ICC have emerged. In most of these studies, laparoscopic surgery has been suggested to be associated with lower morbidity rates, less pain, faster recovery, and shorter hospital stays than conventional open surgery in terms of short-term outcomes ( 12 15 ). However, none of those studies have explored the advantages and disadvantages of the two approaches in terms of short-term outcomes after anatomical hepatectomy.…”
Section: Discussionmentioning
confidence: 99%